2020
DOI: 10.3390/biomedicines8120541
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Temozolomide Affects Locomotor Activity and Cartilage Structure of Elderly Experimental Rats

Abstract: Chemotherapy with temozolomide (TMZ) is an essential part of anticancer therapy of various malignant tumours; however, its long-term effects on patients’ health and life quality need to be further investigated. Here, we studied the effects of TMZ and/or companion drug dexamethasone (DXM) on the locomotor activity and cartilage structure of elderly Wistar rats (n = 40). Long-term TMZ treatment selectively inhibited the horizontal, but not vertical locomotor activity of the rats (6.7-fold, p < 0.01) and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A similar result was shown for rat knee joints, where DXM administration at a dose of 1 mg/kg immediately prior to TNFα injection prevented TNFα-induced degradation of CSPG aggrecan and the release of aggrecanase-generated aggrecan fragments from the articular cartilage into the synovial fluid [ 38 ]. DXM treatment at 2.5 mg/kg for five cycles for 5 consecutive days with breaks of 16 days also attenuated TMZ-induced reorganization of knee joint cartilage structure (increased content of total GAGs and their partial relocalization from chondrocytes into the tissue matrix, as well as a decrease in sulfated GAG content) in elderly Wistar rats [ 39 ]. Triamcinolone acetonide (TA) at doses of 1.25, 2.5, and 5 mg/mL increased PG loss in canine cartilage explants [ 40 ].…”
Section: Effects Of Gcs On Pg Expression and Gag Content In Normal Ti...mentioning
confidence: 99%
“…A similar result was shown for rat knee joints, where DXM administration at a dose of 1 mg/kg immediately prior to TNFα injection prevented TNFα-induced degradation of CSPG aggrecan and the release of aggrecanase-generated aggrecan fragments from the articular cartilage into the synovial fluid [ 38 ]. DXM treatment at 2.5 mg/kg for five cycles for 5 consecutive days with breaks of 16 days also attenuated TMZ-induced reorganization of knee joint cartilage structure (increased content of total GAGs and their partial relocalization from chondrocytes into the tissue matrix, as well as a decrease in sulfated GAG content) in elderly Wistar rats [ 39 ]. Triamcinolone acetonide (TA) at doses of 1.25, 2.5, and 5 mg/mL increased PG loss in canine cartilage explants [ 40 ].…”
Section: Effects Of Gcs On Pg Expression and Gag Content In Normal Ti...mentioning
confidence: 99%
“…However, the effects of TMZ on the behavior of adult and elderly animals have not been sufficiently studied. In a previous conducted by the authors, it was revealed that long-term treatment with TMZ to adult Wistar rats resulted in a significant decrease in their locomotor activity ( 25 ), whereas its effects on the anxiety of the animals remained unknown.…”
Section: Introductionmentioning
confidence: 99%